The Influence of Company-specific Assets on Corporate Performance Interaction - Wei, Shih-Yung; Lin, Li-Wei; Yan, Su-Rong; Zhang, Yun-Han (International Journal of Economics and Financial Issues, 2020)
This paper studies the interaction between the exclusive assets of listed companies (except the financial industry) and the performance of listed companies in Taiwan during the 20 years from 1998 to 2017, and studies the changes of the interaction, and divides the time point into two stages, namely, 1998 (the end of the Asian financial turmoil), 2008 (the beginning of the world financial tsunami) and 2017. In this study, it is found that there is interaction among R & D intensity, marketing intensity and capital intensity. Due to the mutual exclusion of costs, the pairwise effect is almost negative, but the attributes still have additive effect with each other (the interaction of the three attributes is positive). However, in the later period (2008 2017), this study found that the interaction between R & D intensity and marketing intensity showed a positive effect, which can be seen that the investment in R & D in the future is also helpful to the company’s advertising. It is found that when an economy wants to develop internationalization, the degree of internationalization will be a positive effect on corporate performance, and when it reaches a certain degree, the positive effect will disappear and show a nonlinear effect. This study finds that Taiwan shows a W-shaped effect in the later stage of this study. Keywords: Specific asset, interaction panel data, The influence of Company- specific assets on Corporate performance interaction JEL Classifications: C32; O13; O47 DOI: https://doi.org/10.32479/ijefi.10041